Growth and Recovery in Mongolia During Transition - Cheng, Kevin (IMF Working Papers; Working Paper ;, 2003)
This paper studies Mongolia's experience of growth and recovery during the first decade of its transition to a market-based system and compares it with those of other transition economies. Mongolia, like most other transition economies, experienced a painful, initial "transformational recession" before the economy began to recover, with efficiency gains the main source of growth during the early stages of transition. Mongolia's transition process has been relatively smooth compared with other transition economies, probably reflecting the combined effects of some favorable initial conditions, coupled with the early adoption of appropriate adjustment policies and market-oriented reforms.